Age at diagnosis of Type 2 diabetes in Germany: a nationwide analysis based on claims data from 69 million people. Issue 10 (27th August 2019) - Jacobs, E.; Rathmann, W.; Tönnies, T.; Arendt, D.; Marchowez, M.; Veith, L.; Kuss, O.; Brinks, R.; Hoyer, A.
Abstract: Aim: For many European countries, including Germany, no valid estimates are available on age at diagnosis of Type 2 diabetes. Thus, we aimed to estimate the age at diagnosis in Germany. Methods: Age at diagnosis of Type 2 diabetes in Germany was estimated based on Type 2 diabetes prevalence and incidence and the age distribution of the German population. Age‐ and sex‐specific incidence and prevalence in 2014/2015, based on claims data from statutory health insurance ( n = 69 000 000, 85% of the German population), and the age pyramid for Germany in 2015 were used for the calculation. Age at Type 2 diabetes diagnosis was stratified by sex. CIs were estimated using bootstrap methods. In addition, the age range in which 50% of the population received a diagnosis of Type 2 diabetes was calculated (the interquartile range). Results: The mean ± sd age at Type 2 diabetes diagnosis in 2015 was 61.0 ± 13.4 years (95% CI 60.9–61.0) in men. Women were diagnosed 2 years later than men (mean age 63.4 ± 14.9 years; 95% CI 63.4–63.5). The age range in which 50% of the population was diagnosed with diabetes was 53–72 years for men and 54–76 years for women. Conclusions: The sex differences are mainly attributable to a higher incidence of Type 2 diabetes in men than women during middle age and the higher absolute number of women in the older ages. The early age at diabetes diagnosis compared to average life expectancy means that the risk of diabetes‐related complications is increased. What's new?: In Europe, estimates of age at Type 2 diabetes diagnosis are rarely available and are often not representative of the general population. A high proportion of newly diagnosed Type 2 diabetes cases occur in the age group of 60–80 years. The present study found that the mean age at Type 2 diabetes diagnosis was 61.0 ± 13.4 years in men [median (interquartile range) 62 (53–72) years] and 63.4 ± 14.9 years in women [median (interquartile range) 65 (54–76) years]. As a result of increasing life expectancy, a mean age at diagnosis in the early 60s indicates a long diabetes duration, which increases the risk of complications.